1982
DOI: 10.1161/01.res.51.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Pulse wave reflection: can it explain the differences between systemic and pulmonary pressure and flow waves? A study in dogs.

Abstract: SUMMARY. We have studied the effect of changes in pulse wave reflection on the configurations of pressure and flow in systemic and pulmonary circulation. Electromagnetic flow transducers, atrial catheters, and pacing leads were implanted in 10 dogs. In four animals, the flow transducer was placed on the pulmonary artery, in another four on the ascending aorta, and in two additional dogs on both vessels. One week later, ascending aortic and/or pulmonary artery flow and pressure (catheter tip manometer) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…6, June 1984 other dissimilarity is seen in the low frequency range, where the phase angles of the pulmonary impedance spectra are less than in the systemic tree. These results are consistent with less reflection in the pulmonary system (Van den Bos et al, 1982).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…6, June 1984 other dissimilarity is seen in the low frequency range, where the phase angles of the pulmonary impedance spectra are less than in the systemic tree. These results are consistent with less reflection in the pulmonary system (Van den Bos et al, 1982).…”
supporting
confidence: 85%
“…However, these investigators pointed out that loading effects of the external flow transducer may have affected the values of pulmonary characteristic impedance in their study. With serotonin infusion, Bergel and Milnor (1965) and Van den Bos et al (1982) reported no change in characteristic impedance. Bargainer (1967), using pulsewave velocity to calculate characteristic impedance, found an increase with serotonin infusion.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…31,32 Pressure pulse waveform reflections arise primarily from discontinuities in the caliber or elastic properties along vessels in the arterial system, with the major reflection sites located close to the high-resistance arterioles. 33 The decline in the oscillatory compliance estimate was more closely associated with advancing age than a reduction in large artery compliance. Because the arterioles are largely free from atheroma and the change in oscillatory compliance was independent of blood pressure change in this population, this estimate may be a sensitive marker for the effects of the aging process per se independent of other confounding influences.…”
Section: Figurementioning
confidence: 92%
“…The shape of the pressure wave in the normal pulmonary circulation is similar to that of the flow wave. 3 From previous invasive studies in patients without increased PVR, we know that peak flow and peak pressure normally coincide, and there is no increase in pressure after peak flow. 4,5 On the other hand, in patients with pulmonary hypertension due to increased PVR, augmented pressure (AP) after peak flow due to an earlier and more pronounced pressure reflection has been observed.…”
Section: Clinical Perspective On P 432mentioning
confidence: 98%